. Clinical Significance of NLRP3 Inflammasome and Related Cell Moleculesin early Elderly Diabetic Kidney Disease: NLRP3 Inflammasome and Related Cell Moleculesin - Shang, Yan (Journal of Medical Biochemistry, 2024)
Backgrounds：It aims to investigate the expression level of NLRP3 inflammasome and its related cell molecules in early diabetes kidney disease (EDKD) in the elderly and its clinical application value. Methods: From October 2021 to April 2023, 50 elderly patients with T2DM (T2DM group), 50 elderly patients with EDKD (EDKD group) and 50 elderly people who passed the health check-up (healthy group) are chosenas the study subjects. Plasma NLRP3 inflammasome and related cells (blood leukocyte count, monocyte count, lymphocyte count) molecular (NT-proBNP and others) levels are tested, and Pearson correlation analysis is utilized to explore the correlation among plasma NLRP3 inflammasome and related cells, molecules and renal function indicators (UACR, BUN, Ucr) in elderly patients with EDKD. Results: (1) The three groups’ comparison in HbA1c, FIns, HOMA-IR, UACR, BUN, Ucr, SOD, MCP-1 and TNF-α level were with P<0.05.The levels of TG and LDL-C in the EDKD group were bigger than those in the T2DM and the healthy groups;The levels of FPG, HbA1c, FINs, HOMA-IR, UACR, SOD, MCP-1, TNF-α in the EDKD and T2DM groups werebigger than those in the healthy group, while SOD wassmaller than that in the healthy group; The levels of BUN, Ucr, hs-CRP, FPG, HbA1c, FINs, HOMA-IR, UACR, SOD, MCP-1, TNF-α in the EDKD group werebigger than those in the T2DM group, while SOD was smallerthan that in the T2DM group;The aboveresults were with P<0.05. (2)It has P<0.05 in Monocyte count, NLRP3, NT-proBNP, caspase-1, ASC and othersin the three groups.The levels of thosein the EDKD and T2DM groups were bigger than the healthy group. The levels of these indicators in the EDKD group were bigger than those in the T2DM group, and with P<0.05.These indicators in EDKD group were positively correlated with UACR, BUN, and Ucr, respectively, and with P<0.05. Conclusion: NLRP3 inflammasome and its related molecules caspase-1, ASC, IL-1β, IL-18 level and Monocyte count raised in early senile EDKD, and were significantly correlated with the severity of EDKD.